Descriptive Study of Children's Knowledge about Hand Hygiene as a Prevention of the Spread of Covid-19 - Fitrianola Rezkiki; Rahmiwati Rahmiwati; Almarinda Almarinda (Padjadjaran Acute Care Nursing Journal, 2020)
The mortality rate of Covid-19 in Indonesia is 8.9%, which is the highest rate in Southeast Asia. Indonesia announces that there are positive patients with Covid-19 in children under five and school age. Children have the potential to transmit the virus to other people. One of the efforts to prevent the spread of Covid-19 is to carry out hand hygiene according to the Covid-19 protocol. The research objective was to determine the knowledge of school age children about hand hygiene as an effort to prevent the spread of Covid-19. The research design is descriptive analytic. The population in this study were children of elementary school age, namely as many as 403 people. By using Simple Random sampling, the sample were found 100 respondents. The data were collected using a questionnaire that contains knowledge of school age children about hand hygiene. The results showed that 45% of respondents have low knowledge of hand hygiene and 55% of respondents have high knowledge of hand hygiene as an effort to prevent the spread of Covid-19. The lowest respondent's knowledge (46.8%) is about washing hands with the right steps which take a long time. It can be concluded that respondents still have low knowledge about hand hygiene as an effort to prevent the spread of Covid-19. It is hoped that parents and schools will disseminate how to properly practice hand hygiene, and facilitate the availability of a place to wash hands that is equipped with hand washing soap and water flow.